Mechanical Device Malfunction of the HeartMate II Versus the HeartMate 3 Left Ventricular Assist Device: The Rotterdam Experience. Issue 2 (13th December 2022) - van der Heiden, Cornelis W.; Zijderhand, Casper F.; Veen, Kevin M.; Constantinescu, Alina A.; Manintveld, Olivier C.; Brugts, Jasper J.; Bekkers, Jos A.; Birim, Ozcan; Bogers, Ad J. J. C.; Caliskan, Kadir
Abstract : Mechanical device malfunction remains a known issue in left ventricular assist devices (LVADs). We investigated the incidence of mechanical device malfunction in the HeartMate II and HeartMate 3 LVADs. We conducted a retrospective study of all HeartMate II and HeartMate 3 LVADs implanted in our center. We evaluated major malfunction, potential major malfunction, minor malfunction, and need of device exchange. In total, 163 patients received an LVAD; in 63 (39%) a HeartMate II, and in 100 (61%) a HeartMate 3, median support time of respectively 24.6 months (interquartile range [IQR]: 32.4) and 21.1 months [IQR: 27.2]. Mechanical device malfunction, consisting of both major and potential major malfunction, occurred significantly less in the HeartMate 3 patients with a hazard ratio (HR) of 0.37 (95% confidence interval [CI]: 0.15–0.87, p = 0.022). Major malfunction alone occurred significantly less in HeartMate 3 patients with a HR of 0.18 (95% CI: 0.05–0.66, p = 0.009). HeartMate 3 patients had a significantly decreased hazard of a pump or outflow graft exchange (HR 0.13, 95% CI: 0.08–0.81, p = 0.008). System controller defects occurred significantly less in HM 3 patients ( p = 0.007), but battery-clips defects occurred significantly more in HM 3 patients ( p = 0.039). Major device malfunction including pump or outflow graft exchange occurred significantly less in HeartMate 3 compared to HeartMate II, while minor malfunctions were similar. Periodical assessment of the technical integrity of the device remains necessary during long-term LVAD support.